Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Umkm di Wilayah Krapyak Wetan Yogyakarta - Nisa, Silviana Khoerun; Jumadi, Jumadi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of compensation and work environment on the job satisfaction of employees in micro, small, and medium enterprises (MSMEs) in the Krapyak Wetan area of Yogyakarta. The method used is quantitative with Non-Probability Sampling through Purposive Sampling involving one hundred respondents. Data collection was conducted by distributing questionnaires directly to respondents using a Likert scale research instrument. The data were processed using SPSS version 27, and the analyses performed included validity tests, reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing. The results show that collectively, compensation (X1) and work environment (X2) have a significant effect on job satisfaction (Y), with an F calculated value of 124.960, which is greater than the F table value of 3.09, and a significance result of 0.000, which is less than 0.05. Partially, compensation has a significant positive effect with a t calculated value of 8.449, which is greater than the t table value of 1.661, with a significance level of 0.000, which is less than 0.05. Similarly, the work environment also has a significant positive effect with a t calculated value of 5.128, which is greater than the t table value of 1.661, with a significance level of 0.000, which is less than 0.05, thus affecting job satisfaction. The coefficient of determination value of 71.5% indicates that the model can explain job satisfaction moderately.